Norcantharidin promotes cancer radiosensitization through Cullin1 neddylation‐mediated CDC6 protein degradation. Issue 8 (2nd June 2022) - Deng, Tanggang; Zhu, Qianling; Xie, Lin; Liu, Youhong; Peng, Yuchong; Yin, Linglong; Gao, Yingxue; Cao, Tuoyu; Fu, Yuxin; Qi, Xuli; Zhang, Songwei; Peng, Yongbo; et al.
Abstract: Radiotherapy (RT) is a conventional cancer therapeutic modality. However, cancer cells tend to develop radioresistance after a period of treatment. Diagnostic markers and therapeutic targets for radiosensitivity are severely lacking. Our recently published studies demonstrated that the cell division cycle (CDC6) is a critical molecule contributing to radioresistance, and maybe a potential therapeutic target to overcome radioresistance. In the present study, we for the first time reported that Norcantharidin (NCTD), a demethylated form of cantharidin, re‐sensitized radioresistant cancer cells to overcome radioresistance, and synergistically promoted irradiation (IR)‐induced cell killing and apoptosis by inducing CDC6 protein degradation. Mechanistically, NCTD induced CDC6 protein degradation through the ubiquitin‐proteasome pathways. By using small interfering RNA (siRNA) interference or small compound inhibitors, we further determined that NCTD induced CDC6 protein degradation through a neddylation‐dependent pathway, but not through Huwe1, Cyclin F, and APC/C‐mediated ubiquitin‐proteasome pathways. We screened the six most relevant Cullin subunits (CUL1, 2, 3, 4A, 4B, and 5) using siRNAs. The knockdown of Cullin1 but not the other five cullins remarkably elevated CDC6 protein levels. NCTD promoted the binding of Cullin1 to CDC6, thereby promoting CDC6 protein degradation through a Cullin1 neddylation‐mediated ubiquitin‐proteasome pathway. NCTD can be used in combination with radiotherapy to achieve better anticancer efficacy, or work as a radiosensitizer to overcome cancer radioresistance.